2022
DOI: 10.5713/ab.21.0200
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal pH pattern, fermentation characteristics and related bacteria in response to dietary live yeast (Saccharomyces cerevisiae) supplementation in beef cattle

Abstract: Objective: In this study we aimed to evaluate the effect of dietary live yeast supplementation on ruminal pH pattern, fermentation characteristics and associated bacteria in beef cattle.Methods: This work comprised of in vitro and in vivo experiments. In vitro fermentation was conducted by incubating 0, 0.05, 0.075, 0.1, 0.125, and 0.15% active dried yeast (Saccharomyces cerevisiae, ADY) with total mixed ration substrate to determine its dose effect. According to in vitro results, 0.1% ADY inclusion level was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…In the present study, pH values ranged from 7.22 to 7.30 across the treatments, indicating minimal effects on ruminal fermentation since it is associated with gas production, DMD, and VFA concentration [32]. Abnormal ruminal pH, resulting from dysfunctional ruminal acid metabolism, can adversely impact the microbial community structure and lead to life-threatening metabolic disorders, such as acidosis [32].…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, pH values ranged from 7.22 to 7.30 across the treatments, indicating minimal effects on ruminal fermentation since it is associated with gas production, DMD, and VFA concentration [32]. Abnormal ruminal pH, resulting from dysfunctional ruminal acid metabolism, can adversely impact the microbial community structure and lead to life-threatening metabolic disorders, such as acidosis [32].…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, Ma et al ( 21 ) found no statistically significant differences in serum albumin concentration between yeast-supplemented and unsupplemented groups. However, increases in the serum total protein and the serum albumin values can be indicators of greater protein outflow from the rumen because of improved ruminal nitrogen utilisation to synthesise microbial protein ( 29 ). Also, in the same research of which the findings suggested the higher nitrogen use, Zhang et al ( 29 ) found increases in serum total proteins and the serum albumin concentrations in a treated group as consequences of improved ruminal fermentation and feed utilisation efficiency after the administration of yeast supplementation in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, feeding medium chain triglycerides increases preprandial concentrations of glucose in plasma by enhancing glycolytic flux [ 42 , 43 ]. It is also reported that MCFAs offered to ruminants increased that of propionate, an indispensable precursor of gluconeogenesis [ 44 ], in in vitro and in vivo studies [ 45 , 46 ]. Thus, a possible enhancement of glycolysis and/or an increase in concentrations of propionate in the rumen likely account for increased concentrations of glucose in plasma of cows in the OCT group.…”
Section: Discussionmentioning
confidence: 99%